Urgency and Implementation of Experience-Based Islamic Religious Education - Winarno; Muhlisin (Cigarskruie: Journal of Educational and Islamic Research, 2024)
The research conducted on experiential education in the context of Islamic Religious Education (PAI) offers an in-depth perspective on how Western pragmatic approaches can be integrated in education rooted in Islamic values. Using phenomenological methods, the research successfully illustrates that experience-oriented education not only enriches the teaching and learning process but also facilitates students' intellectual and spiritual growth. Through deductive and inductive approaches, this study reveals that teachers play a key role as facilitators in designing dialogic and interactive learning experiences, which ultimately shape students' character and critical thinking skills. The implementation of experiential education in PAI is expected to create a dynamic learning environment where science and Islamic values are combined, ensuring that education is not only limited to the transfer of knowledge but also the formation of a complete and mature person.